Preliminary investigation on cholinesterase activity in Adamussium colbecki from Terra Nova Bay: field and laboratory study - CORSI I.; S. BONACCI; G. SANTOVITO; L. CASTAGNOLO; S. FOCARDI; CHIANTORE, MARIACHIARA (Editore Gordon and Breach Science Publishers Taylor & Francis Limited:Rankine Road, Basingstoke RG24 8PR United Kingdom:011 44 1256 813035, EMAIL: madeline.sims@tandf.co.uk, info@tandf.co.uk, INTERNET: http://www.tandf.co.uk, Fax: 011 44 1256 330245, 2004)
While the inhibition of cholinesterase (ChE) activity as a biomarker of exposure to neurotoxic insecticides is well established in aquatic invertebrates of temperate areas, little is known about organisms from polar regions including Antarctica. Cholinesterase activity was investigated in specimens of the Antarctic scallop, Adamussium colbecki, collected in winter 2000 at Campo Icaro (Ross Sea, Antarctica) for preliminary characterization of a potentially new biomarker. Characterization of various ChE enzymes using specific substrates including an acetylthiocholine iodide (ASCh) and a butyrylthiocholine iodide (BSCh) was performed in gills, digestive gland and adductor muscle of the scallop. The effect of in vivo Zn2þ exposure in gills and digestive gland of A. colbecki was also studied. All the tissues expressed ChE activity (gill>adductor muscle>digestive gland) in accordance with data reported for marine mussels (Mytilus sp.) from temperate areas (1.1–13.8 nmol min1 mg protein1). Significant BSCh-dependent ChE inhibition was also measured with a specific inhibitor, Iso-OMPA. Exposure to Zn2þ does not seem to affect ChE activity in the scallop although some slight differences were observed in substrate specificities (ASCh and BSCh) between treated and untreated organisms. This preliminary study stresses the need for further investigation on ChE activity in A. colbecki as a biomarker for monitoring water contamination in the marine Antarctic environment.